2021
DOI: 10.3390/horticulturae7120558
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Pomegranate, Sugar Apple, and Eggplant Peel Extracts Suppresses Aspergillus flavus Growth and Aflatoxin B1 Biosynthesis Pathway

Abstract: Even though the green revolution was a significant turning point in agriculture, it was also marked by the widespread use of chemical pesticides, which prompted severe concerns about their influence on human and environmental health. As a result, the demand for healthier and more environmentally friendly alternatives to control plant diseases and avoid food spoilage is intensifying. Among the proposed alternatives, food by-product extracts, especially from the most consumed fruits in Egypt, eggplant, sugar app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 93 publications
1
3
0
Order By: Relevance
“…The data obtained revealed that the bio-binder's efficacy ratio depended on the concentration of the used plant and the type of mycotoxins. Our results are in harmony with Becker-Algeri et al ( 2016) and Ismail et al (2021). Those previous works indicated that the efficacy of plant extracts depends on their varieties, quantities and components of a particular plant extract.…”
Section: Effects Of Shacking Processsupporting
confidence: 93%
See 1 more Smart Citation
“…The data obtained revealed that the bio-binder's efficacy ratio depended on the concentration of the used plant and the type of mycotoxins. Our results are in harmony with Becker-Algeri et al ( 2016) and Ismail et al (2021). Those previous works indicated that the efficacy of plant extracts depends on their varieties, quantities and components of a particular plant extract.…”
Section: Effects Of Shacking Processsupporting
confidence: 93%
“…Recently, the use of phenolic compounds in this sense is recognized due to their potential antioxidant properties. They are widely recommended as a safe, applicable and more efficient method than other synthetic agents (Abdelnaby et al, 2022 ; Aladaileh et al, 2020 ; Ismail et al, 2021 ; Pani et al, 2014 ; Youssef, Qari, Behiry, et al, 2021 ; Youssef, Qari, Matar, et al, 2021 ). The antioxidant capacity of phenolic compounds might be due to electron donation and hydrogen atom transfer to free radicals (Dai & Mumper, 2010 ) and chelated trace metals involved in radical development (Ghasemzadeh & Ghasemzadeh, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…49 10 Octadecanoic acid Anti-inflammatory 50 and antioxidant. 51,52 11 Oleic acid Antibacterial 53 , anti-inflammatory, antifungal 54 , and anti-cancer. 54,55 12 Stigmast-5-en-3-ol Antioxidant, anti-cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Khojah et al (2022) recorded that In a cereal composite bar, pomegranate by-products and barley malt grass bioactive collaborate to produce antimycotic and antiaflatoxigenic effects. Pomegranate, sugar apple and eggplant peel extracts also inhibit A. flavus growth and the biosynthesis of aflatoxin B1 (AFB1) (Ismail et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Khojah et al (2022) recorded that In a cereal composite bar, pomegranate by‐products and barley malt grass bioactive collaborate to produce antimycotic and antiaflatoxigenic effects. Pomegranate, sugar apple and eggplant peel extracts also inhibit A. flavus growth and the biosynthesis of aflatoxin B1 (AFB1) (Ismail et al, 2021). Anthrax, Chlamydia, Cholera, Lyme disease, Typhus, Relapsing Fever, Tularaemia, Malaria, Plaque, Syphilis, Respiratory infection, Mycoplasma, Rickettsiae, Streptococcal infection and Acne are among the illnesses that Oxytetracycline (OXY) is frequently used to treat.…”
Section: Introductionmentioning
confidence: 99%